Budgeting for public managers - Swain, John W., 1948-; Reed, B. J. (Burton J.), 1949- (M.E. Sharpe, 2010)
Benefiting from the authors' many years of teaching undergraduate and graduate students and practitioners, here is a clear, comprehensive, practice-oriented text for public budgeting courses. Rather than presenting each budgeting concern in mind-numbing detail, the book offers a commonsensical view of public budgeting and its importance to current and future public managers. The text is designed to show readers how managers relate to budgeting and how their actions make a difference in the operation and performance of public organizations. The book covers the historical development of public b.